Chemical Constituents And Possible Anticancer Properties Of Lawsonia Inermis And Strobilanthes Crispus - Endrini, Susi (2003)

(untitled)
Studies on the cytotoxicity effects, antitumour components and their mechanism of action of S. crispus and L. inermis were carried out in this study. The nutrients and non-nutrients composition of L. inermis were determined to investigate whether the leaves are suitable for herbal tea preparation. The crude protein, ether extract, ash and moisture contents were also determined. Ash samples were further analysed to investigate water insoluble ash, water-soluble ash and alkalinity according to the International standard ISO 1576- 1975 (E) and ISO 1 578- 1975 (E) methods, whereas acid insoluble ash was also determined. Carbohydrate content was determined following the Anthrone method. In fresh L. inermis leaves, the moisture content forms the bulk of tissue weight with a mean value of 69.4%. This plant was found to contain high amounts of minerals, such as potassium (29455 mg/100g), calcium (2654 mg/1 00g), sodium (4094 mg/ 100g), iron (266 mg/100g) and phosphorus (550 mg/ 100g).